Edupreneurship in Islamic Religious Education: An Innovative Strategy to Develop Students' Economic Independence - Ahmad Aji Pangestu Aji; Siti Qomala Khayati; Rhindra Puspitasari; Eri Dwi Cahyanti; Lestari; Eri Susanti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the integration of sharia values into Islamic Religious Education (PAI) learning with an entrepreneurship-based approach in formal educational settings. Using a descriptive qualitative approach, the research explores how sharia principles—such as honesty, trustworthiness, hard work, and social responsibility—can be applied in learning activities that foster students’ entrepreneurial spirit. The results indicate that a PAI learning model integrated with sharia values and entrepreneurial contexts not only enhances students’ religious understanding but also develops independent, ethical, and socially beneficial character traits. The findings recommend the development of a curriculum that integrates religious competence and life skills based on the sharia economic framework to prepare students for global challenges